Modeling the risk of radiation-induced lung fibrosis: Irradiated heart tissue is as important as irradiated lung. Issue 1 (October 2015) - Cella, Laura; D'Avino, Vittoria; Palma, Giuseppe; Conson, Manuel; Liuzzi, Raffaele; Picardi, Marco; Pressello, Maria Cristina; Boboc, Genoveva Ionela; Battistini, Roberta; Donato, Vittorio; Pacelli, Roberto
Abstract Purpose We used normal tissue complication probability (NTCP) modeling to explore the impact of heart irradiation on radiation-induced lung fibrosis (RILF). Materials and methods We retrospectively reviewed for RILF 148 consecutive Hodgkin lymphoma (HL) patients treated with sequential chemo-radiotherapy (CHT-RT). Left, right, total lung and heart dose–volume and dose–mass parameters along with clinical, disease and treatment-related characteristics were analyzed. NTCP modeling by multivariate logistic regression analysis using bootstrapping was performed. Models were evaluated by Spearman Rs coefficient and ROC area. Results At a median time of 13 months, 18 out of 115 analyzable patients (15.6%) developed RILF after treatment. A three-variable predictive model resulted to be optimal for RILF. The two models most frequently selected by bootstrap included increasing age and mass of heart receiving >30 Gy as common predictors, in combination with left lung V5 (Rs = 0.35, AUC = 0.78), or alternatively, the lungs near maximum dose D2% (Rs = 0.38, AUC = 0.80). Conclusion CHT-RT may cause lung injury in a small, but significant fraction of HL patients. Our results suggest that aging along with both heart and lung irradiation plays a fundamental role in the risk of developing RILF.